Evaluating environment and development: Lessons from international cooperation. (January 2014) - Uitto, Juha I.
This article discusses environmental evaluation in the context of national development in developing countries. It makes a case for evaluation to move beyond evaluating individual interventions to assessing the contributions to sustainable development at the national and international levels. It highlights challenges relating to evaluating environment in national development, as well as aggregation and attribution of results from programmes aimed for demonstration and policy influence. The discussion is focused around two concrete cases involving programmes by UNDP and the Global Environment Facility.